A COMPARATIVE STUDY OF A TRANS-CRITICAL CARBON DIOXIDE CYCLE POWERED BY A SINGLE FLASH GEOTHERMAL CYCLE WITH/WITHOUT ECONOMIZER OPERATING MODES - Yashar Aryanfar; Jorge Luis García Alcaraz; Julio Blanco Fernández; Ingrid Iovana Burgos Espinoza; Luis Javier Márquez Figueroa (CT&F Ciencia, Tecnología & Futuro)
Renewable energy, particularly geothermal energy, is on the rise globally. It has been demonstrated that recovering heat lost during geothermal cycles is essential due to the inefficiency of these cycles. This paper pproposes a combined power generation cycle using EES software to model a single-flash geothermal cycle, and a trans-critical carbon dioxide cycle. The study compares the system's performance during its "Without Economizer" and "With Economizer" operational stages. The impact of the economizer on the system's output metrics, including the net power output, energy efficiency, and exergy efficiency, was examined. The results show that the "With Economizer" system's net power output increased from 451.3 kW to 454 kW. The energy efficiency difference between the two systems is based on the first law of thermodynamics, where the value ofthe "Without Economizer" system is 6.036%, and the "With Economizer" system is 6.075%. The system without an economizer had an exergy efficiency value of 26.26%, whereas the system with an economizer reached 26.43%, based on the second law of thermodynamics. Installing the economizer increased the total economic cost rate of the system from 0.225M$/Year to 0.2294M$/Year, which increased the product cost rate from 15.82$/GJ to 16.02$/GJ.